Thermodynamic method of calculation of heat of steam formation for binary mixes - B. A. Arutionov; Yosuf Ahmed Elsadig (Тонкие химические технологии, 2010)
In article results and calculations of heat of binary mixes on the basis of the developed thermodynamic analysis of process of transition a liquid- vapor are presented.